Inclusion of Labor Migrants as a Potential Key Population for HIV: A Nationwide Study from Tajikistan - Brian Kwan; Hamid R. Torabzadeh; Adebimpe O. Akinwalere; Julie Nguyen; Patricia Cortez; Jamoliddin Abdullozoda; Salomudin J. Yusufi; Kamiar Alaei; Arash Alaei (Tropical Medicine and Infectious Disease)
Key populations are particularly vulnerable to human immunodeficiency virus (HIV) infection. Nearly half of Tajikistan’s gross domestic product (GDP) originates from labor migrant transfers. While not officially designated as a key population, over 300,000 migrants return to Tajikistan every year at increased risk for HIV due to absence or interruption of treatment, change in risky behaviors, and other factors. We analyzed cross-sectional data from the national registry system operated by the Tajikistan Ministry of Health and Social Protection of individuals (n = 10,700) who had been diagnosed with HIV from 1 January 2010 to 30 May 2023. Individual HIV cases resided in five regions: Districts of Republican Subordination (DRS), Dushanbe (Tajikistan’s capital city), Gorno-Badakhshan Autonomous Oblast (GBAO), Khatlon, and Sughd. We developed logistic regression models to investigate the relationships between key population status and demographic characteristics. GBAO has the largest proportion of labor migrants (49.59%), which is much larger than that of the other regions (<32%). In contrast to other key populations, there was a larger proportion of HIV cases in rural areas that were labor migrants (23.25%) in comparison to urban areas (16.05%). In multivariable analysis, the odds of being a labor migrant were 6.248 (95% CI: 4.811, 8.113), 2.691 (95% CI: 2.275, 3.184), and 1.388 (95% CI: 1.155, 1.668) times larger if a case was residing in GBAO, Sughd, or DRS, compared to Dushanbe, respectively. Our research contributes to the field by proposing to expand the definition of key population to include labor migrants in Central Asia who should be emphasized as a vulnerable population at high risk of HIV. We encourage policy action to provide designated HIV funding for labor migrants, increase international attention, and promote potential modifications of national regulations and/or laws regarding prevention and treatment of HIV among non-citizen populations.